Studi Deskriptif Tentang Peran Guru sebagai Fasilitator Literasi Numerasi dalam Pembelajaran Matematika di Kelas Rendah MI/SD - Dian Ika Safitriana; Kamilatul Fatiyah; Umi Mahmudah (Pusat Riset dan Inovasi Nasional, 2025)
Elementary education plays a pivotal role in shaping students’ cognitive, affective, and psychomotor development. Among the essential 21st-century skills, numeracy literacy is crucial for enabling students to interpret and utilize quantitative information in real-life contexts. Despite its importance, international assessments such as PISA indicate that Indonesian students’ numeracy skills remain low. This study aims to explore the role of teachers as facilitators in promoting numeracy literacy through mathematics instruction in lower elementary grades (grades I–III) at Madrasah Ibtidaiyah. Employing a qualitative descriptive approach, data were collected through classroom observations, in-depth interviews, and document analysis at MIS Wonoyoso, involving three teachers with over three years of experience. The findings reveal that although lesson planning aligns with the curriculum, it remains focused on procedural skills and lacks contextual and conceptual depth needed for numeracy development. Teachers demonstrated limited understanding of numeracy as a broader cognitive ability beyond basic arithmetic. Challenges identified include time constraints, lack of resources, and limited professional training. The study concludes that to effectively function as facilitators of numeracy literacy, teachers need continuous professional development, contextual teaching strategies, and collaborative platforms to reflect on and enhance numeracy-focused instruction. Strengthening these areas is essential for fostering students' logical reasoning and problem-solving abilities from early education.